DIVERSIFICATION OF COCONUT FRUIT INTO A SUPERIOR PRODUCT IN SIDAMULIH VILLAGE, PANGANDARAN REGENCY, WEST JAVA PROVINCE - Tini, Sumartini; Suliasih, Neneng; Hervelly, Hervelly; Azzahra, Raisa; N.M, Sarah (LPPM Univ. Ibn Khaldun Bogor, 2023)
Coconuts in Sidamulih Village have great potential in marketing and producing coconuts not only in the form of fresh fruit but in processing production (diversification). The purpose in this community service is to increase production not only in the form of fresh coconuts but in the form of various processed food products. The method is implemented with the mentoring method. The results obtained gained knowledge about coconut processing in several products, namely: oil with the sour method, candied coconut, coconut water drinks and coconut water cocrystals. The existence of universities in carrying out community service activities has at least three things built, namely increased knowledge, increased skills and increased business motivation. MSME groups in the Sidamulih area have one of the potentials to foster an attitude of community independence towards a better economy. The specific target that also wants to be achieved is to provide science / technology about Coconut Diversification into products of economic value to the community, especially in MSME groups, especially those in the Sidamulih Village area, Pangandaran Regency.